AUDIT MANAJEMEN UNTUK MENILAI EFEKTIVITAS FUNGSI SUMBER DAYA MANUSIA (Studi Kasus pada Rumah Sakit Islam Aisyiyah Malang) - Riska Agustin Widya Pradana; Nurul Fachriyah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The research aimed at knowing the effectiveness level of human resources function implementation, knowing the obstacles in reaching effectiveness and giving repair recommendation to improve the effectiveness. The research used case study research with descriptive method. The data were obtained by questionnaires, interview, and observation. The result showed that from the ten human resources function under research, nine function run effectively. The nine functions such as human resources planning, procedure ad process of recruitment, human resources selection, orientation and placement, training and development of human resources, achievement evaluation, management of compensation system, employee protection, and dissolution of work relationship. But one of the function programs of work achievement valuation is considered as not effective yet, that was the paragon worker selection. While one function that is not effective yet is the career development plan function. There are obstacles and weaknesses found so it is proposed some correction recommendations. Keywords: Management audit, Effectiveness, Human Resources